2017
DOI: 10.1111/joa.12674
|View full text |Cite
|
Sign up to set email alerts
|

Restricted co‐localization of glutamate and dopamine in neurons of the adult sea lamprey brain

Abstract: Co-localization of dopamine with other classical neurotransmitters in the same neuron is a common phenomenon in the brain of vertebrates. In mammals, some dopaminergic neurons of the ventral tegmental area and the hypothalamus have a glutamatergic co-phenotype. However, information on the presence of this type of dopaminergic neurons in other vertebrate groups is very scant. Here, we aimed to provide new insights on the evolution of this neuronal co-phenotype by studying the presence of a dual dopaminergic/glu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 46 publications
1
8
0
Order By: Relevance
“…Although several factors can affect this estimation (e.g., detection method and threshold), the lamprey SNc/VTA shows a high vGluT-to-TH ratio and a high co-expression of vGluT and dopamine (Figures 1F and 1G; Table 1). Previous studies did not find co-localization of dopamine and glutamate or GABA [26,27], most likely due to low sensitivity of the used methods. However, a recent study indicated co-expression of glutamate and dopamine in lamprey SNc/VTA neurons [28].…”
Section: Most Dopaminergic Snc/vta Neurons Co-express Glutamatementioning
confidence: 86%
See 1 more Smart Citation
“…Although several factors can affect this estimation (e.g., detection method and threshold), the lamprey SNc/VTA shows a high vGluT-to-TH ratio and a high co-expression of vGluT and dopamine (Figures 1F and 1G; Table 1). Previous studies did not find co-localization of dopamine and glutamate or GABA [26,27], most likely due to low sensitivity of the used methods. However, a recent study indicated co-expression of glutamate and dopamine in lamprey SNc/VTA neurons [28].…”
Section: Most Dopaminergic Snc/vta Neurons Co-express Glutamatementioning
confidence: 86%
“…We next examined whether TH/vGluT-immunopositive terminals from the SNc/VTA are present in the striatum and tectum. Tracer injections into the SNc/VTA ( Figure 3A) combined with immunohistochemistry for vGluT and TH showed that many TH/vGluT fibers originating from the SNc/VTA are present in the striatum (see also [26]; Figure 3B, arrowheads; N = 3). These results suggest that, as in mammals [7], dopamine and glutamate may be co-released in the striatum.…”
Section: Fibers Co-expressing Dopamine and Glutamate Are Found In Strmentioning
confidence: 98%
“…Here, the possibility that dopamine (DA) could modulate olfactory processing taking place in the medOB was examined. Dopaminergic processes and cells were previously observed in the OB of lampreys (Barreiro‐Iglesias, Villar‐Cervino, Anadon, & Rodicio, ; Fernandez‐Lopez, Sobrido‐Camean, Anadon, Rodicio, & Barreiro‐Iglesias, ; Pierre, Mahouche, Suderevskaya, Reperant, & Ward, ; Pierre, Rio, Mahouche, & Repérant, ; Pombal, El Manira, & Grillner, ), as in every other vertebrate studied (Smeets & Gonzalez, ). Also, cells expressing D1 or D2 receptors have been observed in the OB (Pérez‐Fernández, ; Pérez‐Fernández et al, ).…”
Section: Introductionmentioning
confidence: 82%
“…For the nomenclature of brain regions and brain nuclei we followed the nomenclature used by our group in recent studies on the organization of different neuronal systems (including neuropeptidergic systems) in the sea lamprey brain (Barreiro-Iglesias et al, 2017; Fernández-López et al, 2017). In some instances, equivalencies to nomenclatures used by other authors are mentioned in the results and discussion.…”
Section: Methodsmentioning
confidence: 99%